The effectiveness of mindfulness-based interventions among cancer patients and survivors: a systematic review and meta-analysis - Xunlin, NG; Lau, Ying; Klainin-Yobas, Piyanee (Supportive care in cancer, 2020)
Purpose Cancer is one of the leading causes of morbidity and mortality worldwide. Cancer negatively affects individuals’ quality of life and overall health. Mindfulness-based interventions appear to be promising in the reduction of cancer-related and treatment-related symptoms. This review aimed to systematically summarize and synthesize the best available evidence concerning the effectiveness of mindfulness-based interventions on anxiety, depression, quality of life, fatigue, stress, posttraumatic growth, and mindfulness among adult cancer patients and survivors. Methods A literature search was conducted across 10 electronic databases. Only randomized controlled trials were eligible. Two reviewers independently screened the studies, extracted data, and performed quality assessment using the Cochrane risk of bias assessment tool. Meta-analyses were conducted using review manager software, and standardized mean difference (SMD) was used to determine intervention effects. Subgroup analyses were performed for cancer type, gender, and interventions. Heterogeneity was examined using the Chi 2 and I 2 statistics. Results Twenty-nine studies were included with a total of 3476 participants. Those who received mindfulness-based interventions reported significantly lower anxiety, depression, fatigue, and stress and greater quality of life, posttraumatic growth, and mindfulness than respondents in control groups. Mindfulness-based art therapy (MBAT) produced the strongest intervention effect on anxiety (SMD = − 2.48) and depression (SMD = − 2.21), followed by mindfulness-based stress reduction program (MBSR) and mindfulness-based care recovery (MBCR). The interventions were effective across different cancer types. Conclusion Mindfulness-based interventions can be used as an adjuvant therapy for the management of cancer-related symptoms among cancer patients and survivors.